Qualitative Detection of Kaempferol and Myricetin from Euphorbia indica L. - G.M.Rathod4and V.L.Deshmukh5, A.A.Waghmare1*, V.T.Narwade2, R.G.Ladda3 (Journal of Ecobiotechnology, 2010)
Present paper deals with the qualitative detection of flavonoids like kaempferol and myricetin from Euphorbia Indica L. by Thin Layer Chromatography (TLC) and spectroscopic method. — 1Sidharth College, Jafrabad Dist.Aurangabad (M.S.), India 2Bahirji Smarak Mahavidyalaya, Basmathnagar Dist. Hingoli (M.S.), India 3S.J.College, Gangakhed Dist. Parbhani (M.S.), India 4S.K.M.,GunjotiÂ Dist. Osmanabad, (M.S.), India 5D.S.M.College Parbhani, (M.S.), India — Please Cite This Article As: A.A.Waghmare, V.T.Narwade, R.G.Ladda, G.M.Rathod and V.L.Deshmukh. 2010. Qualitative Detection of Kaempferol and Myricetin from Euphorbia indica L. J. Ecobiotechnol. 2(6):56. Â